1999
DOI: 10.1021/jp9842392
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Endoergic Bimolecular Proton Transfer Reactions:  F-+ ROH → HF + RO-(R = H, CH3, CH3CH2, (CH3)2CH, and (CH3)3C)

Abstract: Guided ion beam tandem mass spectrometry techniques are used to measure reaction threshold energies for proton transfer of water, methanol, ethanol, 2-propanol, and 2-methyl-2-propanol with fluoride anion, F- + ROH → RO- + HF, where R = H, CH3, CH3CH2, (CH3)2CH, or (CH3)3C. The measured reaction threshold energy is an upper limit for the gas-phase acidity of the alcohol relative to hydrogen fluoride. Our guided ion beam measurements yield threshold energies that are consistently higher than those based on curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 83 publications
4
23
0
Order By: Relevance
“…The observed OO frequency in ice I is 220 cm −1 3. This frequency increases to 1063 cm −1 in the HO − ⋅⋅⋅HOH complex, which compares very well with the value of 1082 cm −1 reported in the literature 59. A poorer agreement is found between the LS and ab initio ω NN frequencies of the (NH 3 ) 2 dimer (212 and 103 cm −1 , respectively)60 and for the (HF) dimer (197 and 160 cm −1 , respectively).…”
Section: Resultssupporting
confidence: 89%
“…The observed OO frequency in ice I is 220 cm −1 3. This frequency increases to 1063 cm −1 in the HO − ⋅⋅⋅HOH complex, which compares very well with the value of 1082 cm −1 reported in the literature 59. A poorer agreement is found between the LS and ab initio ω NN frequencies of the (NH 3 ) 2 dimer (212 and 103 cm −1 , respectively)60 and for the (HF) dimer (197 and 160 cm −1 , respectively).…”
Section: Resultssupporting
confidence: 89%
“…Rotational constants and vibrational frequencies for the complexes and products were computed at the HF/6-31G(d) level using Gaussian 94, and vibrational frequencies are scaled by 0.8953 . Table lists the calculated frequencies for the complexes; product molecule frequencies have been reported previously . Low-frequency torsional motions can be treated as harmonic oscillators, free rotors, or hindered rotors.…”
Section: Methodsmentioning
confidence: 99%
“… The threshold energy difference between the two reaction channels in reaction 3 is related to the gas-phase acidity of the alcohol by eq 4 The approximation on the right-hand side of eq 4a assumes that there are no reverse activation barriers for the two dissociation channels, which is reasonable for most proton-bound complexes . To extract the two threshold energies, the energy-dependent branching ratio between the two channels is modeled explicitly using the RRKM theory model developed recently by Rodgers and Armentrout .…”
Section: Introductionmentioning
confidence: 99%
“…Viggiano and Morris have concluded that rotational and translational energy are equally available for driving slightly endothermic charge transfer processes [58]. In other cases, the precision afforded by analysis of competitive CID processes (see below) has permitted evaluations which suggest that rotational energy is not active in promoting proton transfer reactions [59,60]. At present, there are no guiding principles that elucidate which systems should or should not include rotational energy.…”
Section: Internal Energy Of the Reactants: Rotationalmentioning
confidence: 99%